Challenging arthroscopic management of ankle synovial chondromatosis: A case report - Tarek N Fetih; Ahmed A Mekhemar; Rashed M Hashad (Journal of Orthopaedics, Trauma and Rehabilitation)
Synovial chondromatosis (SC) is a rare benign disorder characterized by the presence of metaplastic cartilage nodules originating from the synovial lining of joints, bursa, and tendon sheaths. The treatment option is usually open surgery for excision of loose bodies and synovectomy, while on literature review only few cases with arthroscopic management are reported. We present a 28-year-old male patient who was evaluated for pain, swelling, and limited range of motion of the right ankle joint. Both physical examination and radiographic investigations were suggestive of primary SC of the ankle joint and arthroscopic surgery was performed. Removal of loose bodies and synovectomy were successfully performed. Histopathology confirmed the diagnosis. SC of the ankle is a rare disorder, and its treatment strategies depend on patient complaint, age, and the stage of the disease. Open or arthroscopic surgery can be performed. This case report suggests that arthroscopic management can provide successful outcome in such cases.